Direct Hair Transplantation: A Modified Follicular Unit Extraction Technique - Sethi, Pradeep (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: In hair transplantation, the survival rate of harvested grafts depends upon many factors like maintenance of hydration, cold temperature, reduced mechanical handling and asepsis. All these factors are favourably improved if time out of body is reduced significantly. We have tried a modification called direct hair transplantation in the existing follicular unit extraction technique, in which the follicular unit grafts are implanted as soon as they are harvested. In this article, we have described the detailed methodology and a series of 29 patients who underwent direct hair transplantation. AIM: To evaluate the efficacy and feasibility of direct hair transplantation. SUBJECTS AND METHODS: The patients willing to undergo hair transplantation by the technique of follicular unit extraction were enrolled for the surgery. After administration of local anaesthesia, the recipient sites were created. Thereafter, the processes of scoring the skin with a motorized punch, graft extraction and implantation were performed simultaneously. These patients were followed up to look for the time period of initiation of hair growth, the growth achieved at the end of 6–8 months and any adverse events. The results of patients with noticeable improvement in the photographs and reduction in baldness grade were taken as ‘good’, whereas, in other patients, it was classified as ‘poor’. RESULTS: All patients were males with age ranging from 21 to 66 years (median 30 years). Twenty-six patients had androgenetic alopecia, 1 patient had traction alopecia and 2 patients had scarring alopecia. Twenty-seven patients showed ‘good’ results, whereas 2 patients showed ‘poor’ results. CONCLUSION: Direct hair transplantation is a simple and feasible modification in the follicular unit extraction technique. It is an efficacious surgical treatment modality for baldness.